Hydrogeochemical Assessment of Groundwater Quality and Geological Influence in Igarra and environs, Southwestern Nigeria - S. A. Salami; O. G. Akperi (Journal of Applied Sciences and Environmental Management, 2023)
The impact of Geology on groundwater is not fully appreciated in many Nigerian groundwater quality literature. This study investigates the influence of Geology on the hydrogeochemical makeup of groundwater in Igarra and environs, Nigeria. Igarra and environs is underlain by metasediments intruded by Pan African Granites. Ten water samples were collected and analyzed in the laboratory to determine their chemical composition. The results revealed that the pH of most samples was slightly acidic to mainly alkaline, with high electrical conductivity (EC) and total dissolved solids (TDS) values. Correlation and regression analyses showed that the TDS, EC, salinity, chemical oxygen demand, dissolved oxygen, and major and minor constituents positively influenced the pH of the groundwater. Hierarchical cluster analysis demonstrated that the water samples had different compositions and concentrations based on local geological influences. The water samples from Granite, Quartzites, Migmatites and Gneiss rock types shared similar characteristics and had a lower concentration of minerals than the water samples taken from the Quartz Mica Schists and Metaconglomerates. The water in Igarra was predominantly Magnesium Bicarbonate type. However, some of the water samples exceeded the drinking standards for TDS, EC, Cl, Fe, Cr, Cd, and Pb. The study recommends the inclusion of biological parameters to gain a clearer picture of the water quality, particularly from the anthropogenic point of view.